MINDFULNESS-BASED STRESS REDUCTION (MBSR) AND EFFECTIVENESS ON ANXIETY IN BREAST CANCER SURVIVORS: A RAPID LITERATURE REVIEW - Witdiawati, Witdiawati; Andini, Wilda; Purnama, Dadang; Dinan, Nur Azmina; Bakar, Shabila Fasa Noor; Fauziah, Siti; Mulyani, Airin Rizki (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2025)
Cancer is one of the leading causes of death in the world and its number continues to increase every day. The decline in physical condition that haunts breast cancer patients often makes patients anxious. Mindfulness-based stress reduction (MBSR) has been used to cope with stress normally but often and more significantly than daily life. The purpose of this literature review was to provide an empirical basis to evaluate whether the MBSR method can effectively reduce anxiety levels in breast cancer patients. The method in searching for article data sources was carried out through the Google Scholar, PubMed, SAGE Journals, and EBSCO (2012-2022) data bases database to retrieve relevant articles. The inclusion study design focuses on breast cancer patients. The selection process used the PRISMA Flow Diagram 2009, 5 articles were selected as the result of the selection. Result. MBSR has been shown to be effective in reducing anxiety and stress in breast cancer survivors. Conclusion. MBSR may be one of the nonpharmacological interventions that accompany conventional therapy in breast cancer patients. Keywords: Mindfulness-based stress reduction (MBSR), breast Cancer, Anxiety.